Laporan Kasus Acrodermatitis Enteropathica pada Anak 5 Tahun dengan Level Zink Serum Normal - Nareswari, Adniana; Mochtar, Moerbono; Widhiati, Suci; Kusumawardani, Arie; Ellistasari, Endra Yustin; Julianto, Indah (MEDICINUS, 2021)
Acrodermatitis enterophatica (AE) is an inherited or acquired condition associated with zinc malabsorption. Clinical symptoms of AE are periorificial and acral dermatitis, alopecia, and diarrhea. Serum zinc levels usually decrease in AE patients. A 5-year-old boy presented with crusted erosion on the face, trunks and extremities that have been appeared for one year and worsened last month. It also accompanied by hair and eyebrow loss, diarrhea, and eating disorder. Patient was also malnourished. Dermatovenereology examination showed papules, patches, multiple erythematous plaques with squama, erosions with brownish yellow crust above located on perioral, periorbital, posterior trunk, inguinal, perianal, cubital, popliteal and dorsum pedis region. The oral region showed stomatitis and cheilitis. The orbital region showed conjunctival injection and eye discharge. The scalp, eyebrows and lashes showed total alopecia. Laboratory test showed normal serum zinc levels and decreased levels of alkaline phosphatase. The patient was diagnosed with acquired form of AE. Clinical improvement was seen after zinc supplementation. The diagnosis of AE cannot be made only by low serum zinc levels. If a classical triad of AE was found, we must be able to recognize it immediately, thus prompt and appropriate therapy could be given.